High throughput phenotyping of left and right ventricular cardiomyopathy in calcineurin transgene mice - Moreth, Kristin; Katus, Hugo; Bekeredjian, Raffi; Lehmann, Lorenz (The international journal of cardiovascular imaging, 2015)
Consistent protocols for the assessment of diastolic and systolic cardiac function to assure the comparability of existing data on preclinical models are missing. Calcineurin transgene (CN) mice are a preclinical model for hypertrophic and failing hearts. We aimed at evaluating left and right ventricular structural and functional remodeling in CN hearts with an optimized phenotyping protocol. We developed a protocol using techniques and indices comparable to those from human diagnostics for comprehensive in vivo cardiac screening using high-frequency echocardiography, Doppler, electrocardiography and cardiac magnetic resonance (CMR) techniques. We measured left and right ventricular dimensions and function, pulmonary and mitral flow pattern and the hearts electrophysiology non-invasively in <1 h per mouse. We found severe biventricular dilation and a drastic decline in performance in accordance with a condition of heart failure (HF), diastolic dysfunction and defects in electrical conduction in 8-week-old calcineurin transgenic mice. Echocardiography of the left ventricle was performed with and without anesthesia. In all cases absolute values on echocardiography compared with CMR were smaller for LV dimension and wall thickness, resulting in higher fractional shorting and ejection fraction. The study protocol described here opens opportunities to assess the added value of combined echocardiography, Doppler, CMR and ECG recording techniques for the diagnosis of biventricular cardiac pathologies i.e. of HF and to study symptom occurrence and disease progression non-invasively in high-throughput. Phenotyping CN hearts revealed new symptom occurrence and allowed insights into the diverse phenotype of hypertrophic failing hearts.